Peranan Orang Tua dalam Meningkatkan Prestasi Belajar Anak di MI Mathlabul Ulum - Rif'atus Sholihah; Alfi Zaini Maghfiroh; Fadilul Musta'an (AJER: Advanced Journal of Education and Religion, 2025)
This study aims to examine the role of parents in improving children's learning outcomes. The role of parents is very important in creating an atmosphere that supports the learning process of children, both at home and in their interactions with school. The results of the study showed that emotional support from parents, including motivation and attention, can increase children's confidence and encourage them to study harder. In addition, parental involvement Supporting children in their studies, creating a conducive learning environment, and being a good role model have a positive impact on children's academic success. Communication with teachers also makes it easier for parents to monitor their child's development so that they can provide support that is better suited to their needs. In general, the active role of parents greatly influences children's academic success, as well as the formation of good study habits. Therefore, collaboration between parents and schools to support children's education is very important to achieve optimal learning outcomes.